THE EFFECT OF EXECUTIVE COMPENSATION CONTRACT REFERENCE POINT AND ITS INFLUENCE ON INEFECTIVE INVESTMENT AND FINANCIAL PERFORMANCE - Jiang, Yonghao (Chinese Journal of Social Science and Management, 2020)
The executive compensation contract is crucial to coordinating the interests of all parties as well as alleviating the principal-agent problem. According to the fair preference theory, managers will judge whether they are treated fairly or not by comparing their ability and salary, thus affecting their behavior. To explore the impact of executive compensation on executives' behavior, this study selected the financial data of listed companies from 2012 to 2016 as the sample. Through empirical analysis, it was found that unfair compensation makes executives feel jealous. This unreasonable emotional suggestion reduced their work enthusiasm or increased personal income through over-investment, so the executive compensation contract reference point will enhance inefficient investments, the greater the intensity of inefficient investment, the worse the impact on corporate financial performance.